Identification and characterization of 5α-cyprinol-sulfating cytosolic sulfotransferases (Sults) in the zebrafish (Danio rerio). Issue 174 (November 2017) - Kurogi, Katsuhisa; Yoshihama, Maki; Horton, Austin; Schiefer, Isaac T.; Krasowski, Matthew D.; Hagey, Lee R.; Williams, Frederick E.; Sakakibara, Yoichi; Kenmochi, Naoya; Suiko, Masahito; Liu, Ming-Cheh
Highlights: Zebrafish homogenates are capable of sulfating 5α-cyprinol with a high affinity. Zebrafish Sult2 and Sult3 members exhibit strong 5α-cyprinol-sulfating activities. Zebrafish Sult2 members are more catalytically efficient toward cyprinol than zebrafish Sult3 members. The catalytic property of human SULT2A1 is comparable to that of zebrafish Sult3 members, but not zebrafish Sult2 members. Abstract: 5α-Cyprinol 27-sulfate is the major biliary bile salt present in cypriniform fish including the zebrafish (Danio rerio). The current study was designed to identify the zebrafish cytosolic sulfotransferase (Sult) enzyme(s) capable of sulfating 5α-cyprinol and to characterize the zebrafish 5α-cyprinol-sulfating Sults in comparison with human SULT2A1. Enzymatic assays using zebrafish homogenates showed 5α-cyprinol-sulfating activity. A systematic analysis, using a panel of recombinant zebrafish Sults, revealed two Sult2 subfamily members, Sult2st2 and Sult2st3, as major 5α-cyprinol-sulfating Sults. Both enzymes showed higher activities using 5α-cyprinol as the substrate, compared to their activity with DHEA, a representative substrate for mammalian SULT2 family members, particularly SULT2A1. pH-Dependence and kinetics experiments indicated that the catalytic properties of zebrafish Sult2 family members in mediating the sulfation of 5α-cyprinol were different from those of either zebrafish Sult3st4 or human SULT2A1. Collectively, these results imply that both Sult2st2 and Sult2st3 have evolved to sulfate specifically C27 -bile alcohol, 5α-cyprinol, in Cypriniform fish, whereas the enzymatic characteristics of zebrafish Sult3 members, particularly Sult3st4, correlated with those of human SULT2A1.